Bases neurais dos valores humanos: Efeito da neuromodulação nos valores e comportamentos - Athayde, Rebecca Alves Aguiar (2015)
This thesis aimed to verify the neurobiological bases of human values. As specific objectives, we sought to: 1) verify, via meta-analysis, the average effect size of studies using transcranial direct-current stimulation (tDCS) and their effect on behavior; 2) verify whether Neuromodulatory effects via non-invasive transcranial stimulation alter scores on implicit measures of human values; 3) check whether the neuromodulation produces behavioral changes; and 4) verify if the scores on implicit measures of human values, after stimulation, correlate with the behavioral variables. To this end, four studies were carried out. Study 1 aimed to carry out a systematic review and a meta-analysis on studies of transcranial direct-current stimulation (tDCS) in the region of the dorsolateral prefrontal cortex (DLPFC) and temporoparietal junction (JTP) and their effects on social variables. A total of 2814 articles were found, among them 17 studies were selected, which demonstrated the lack of research linking brain areas and social variables. It was also possible to observe a low effect size (r = -0.07). In turn, Study 2 aimed to build and knowing evidences of factor validity and criterion, and the internal consistency of the behavioral dispositions scale. The study included 352 people, mostly female, with a mean age of 28.2 years. It performed a principal components analysis setting the extraction of six factors, considering only the four items with higher saturation in each factor. Thus, the scale factor validity has been confirmed, and the final measurement consisted of 24 items. Moreover, it proved scale’s discriminant and convergent validity with alphas greater than 0.69 to all factors. Studies 3 and 4 were experimental, using the neuromodulation of non-invasive nature (Transcranial Direct Current Stimulation). In Study 3 we sought to determine whether neuromodulatory effects of the dorsolateral prefrontal cortex (DLPFC) imply a change in the implicit normative and excitement subfunctions scores as well as the related behavioral task (Balloon Analog Risk Task). The study included 45 people, and 64.4% were female and the mean age was 26.9 years, who answered: Single Categorie IAT for Human Values (SC-IAT-values) computerized version, Basic Values Questionnaire (Gouveia, 2003) and Behavioral Dispositional Questionnaire. Analysis of variance allowed verifying a negative relationship between the DLPFC and excitement values, i.e., the inhibition of this area had an effect on these values and subsequent behavior. In fact, the neuromodulation effect was observed to both implicit [F (2) = 4.22; p <0.05] and the behavioral level [F (2) = 3.23; p < 0.05]. In Study 4 aimed verifying that the temporoparietal junction Neuromodulatory effects imply a change in the implicit normative and excitement subfunctions scores as well as the related behavioral task (Balloon Analog Risk Task). The study included 45 people, being 66.7% female and the mean age was 25.5 years, who answered the same measures of the previous study. A variance analysis verified a relationship between the temporoparietal junction and normative values [F (2) = 3.84; p <0.05]; behavioral measure also showed significant differences [F (2) = 3.48; p <0.05], indicating the effect of stimulation. Finally, it is expected that the results presented and discussed in this thesis can contribute to the academic community, specifically in the field of social neuroscience, social psychology and cognitive psychology.